Clinical value of seven autoantibodies combined detection in the diagnosis of lung cancer - Mu, Yinyu (J Clin Lab Anal, 2020)
BACKGROUND: To analyze the clinical value of seven autoantibodies (p53, PGP9.5, SOX2, GAGE7, GBU4‐5, MAGE A1 and CAGE) in lung cancer patients. METHODS: ELISA was used to determine serum levels of seven autoantibodies in 177 patients with lung cancer, 201 healthy persons, and 210 patients with benign pulmonary diseases. Positive rates of 7 autoantibodies were analyzed; receiver operating characteristic (ROC) curves were drawn to analyze their diagnostic efficiency in lung cancer and to compare the positive rate of seven kinds of autoantibody combined detection of lung cancer patients with different clinicopathological features. RESULTS: The positive rate of seven autoantibodies in all subjects was 13.44%. The positive rate of seven autoantibodies in lung cancer was 25.42%. The positive rate of the combined detection of seven autoantibodies in the lung cancer group was significantly higher than that in healthy control group (χ(2) = 19.76, P < .001) and benign lung disease group (χ(2) = 21.44, P < .001). Sensitivity, specificity, and AUC(ROC) of the seven autoantibodies were 25.42%, 91.75%, and 0.683, respectively. Sensitivity and AUC(ROC) were higher than those of the single autoantibody detection. Positive rates of seven autoantibodies in different pathological types and clinical stages of lung cancer patients were significantly different (P < .05). CONCLUSIONS: The combined detection of 7 autoantibodies in lung cancer has some clinical value for the auxiliary diagnosis of lung cancer.